The little book of management bollocks why be human when you could be a manager? - Beaton, Alistair (London Pocket, 2001)
Showing the same incisive and outrageous wit as in his previous books, where he first took on the self-help craze then New Labour's addiction to spin, Alistair Beaton now tackles the management gurus. Read this book and you will be transformed overnight into a successful modern manager, capable of talking authentic management bollocks at any hour of the day or night, because, let's face it, talking bollocks is what modern management is all about. Below are a few of the gems contained within THE LITTLE BOOK OF MANAGEMENT BOLLOCKS...RISK MANAGEMENT Improve risk management outcomes by never investing in anything. INSPIRING OTHERS As a manager, it's your job to inspire others. If there's nothing inspiring about you, just use fear instead.
Keywords: Success in business --